2017
DOI: 10.1038/lsa.2017.117
|View full text |Cite
|
Sign up to set email alerts
|

Four-dimensional light shaping: manipulating ultrafast spatiotemporal foci in space and time

Abstract: The spectral dispersion of ultrashort pulses allows the simultaneous focusing of light in both space and time, which creates so-called spatiotemporal foci. Such space–time coupling may be combined with the existing holographic techniques to give a further dimension of control when generating focal light fields. In the present study, it is shown that a phase-only hologram placed in the pupil plane of an objective and illuminated by a spatially chirped ultrashort pulse can be used to generate three-dimensional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
74
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(75 citation statements)
references
References 49 publications
1
74
0
Order By: Relevance
“…The main concept behind it is to decouple the light shaping into two completely independent steps: a first beam-shaping unit generates and focuses a desired 2D shape on the TF grating; in a second step a SLM, placed after the grating, axially and laterally multiplexes the 2D shape creating a 3D distribution of an arbitrary number of replicas. A similar multiplexing scheme was recently 20 used to replicate GPC shapes in 1P regime 50 , or temporally focused low-NA Gaussian beams 51 . In the former case, the lack of 2PE and TF limited the achievable axial resolution, whereas in the latter the method was restricted to the generation of a static and single-size Gaussian spot.…”
Section: Introduction 30mentioning
confidence: 99%
“…The main concept behind it is to decouple the light shaping into two completely independent steps: a first beam-shaping unit generates and focuses a desired 2D shape on the TF grating; in a second step a SLM, placed after the grating, axially and laterally multiplexes the 2D shape creating a 3D distribution of an arbitrary number of replicas. A similar multiplexing scheme was recently 20 used to replicate GPC shapes in 1P regime 50 , or temporally focused low-NA Gaussian beams 51 . In the former case, the lack of 2PE and TF limited the achievable axial resolution, whereas in the latter the method was restricted to the generation of a static and single-size Gaussian spot.…”
Section: Introduction 30mentioning
confidence: 99%
“…When optimal irradiation parameters are used, the laser-induced modification enhances the local etchability of the silica by up to three orders of magnitude [15,16], allowing the laser-inscribed material to be subsequently removed in a second, chemical etching step. Within the last two decades, collaborative efforts towards better understanding the light-matter interactions [17][18][19] and chemical etching mechanisms [20] and advanced writing techniques [21,22] have established ULAE as a capable manufacturing method for complex glass microcomponents and systems [23,24]. Recently, ULAE has shifted away from using the widely adopted but notoriously hazardous etching agent hydrofluoric acid (HF) to potassium hydroxide (KOH), making the technique much more appealing for industry-level manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…This was done either by generating multiple diffraction-limited spots that were scanned simultaneously across multiple cell somata [18][19][20] , or by using computer generate holography (CGH) to produce light patterns covering multiple cell somata at once 21 , thus optimizing the temporal precision of the photostimulation 22 . Recently, several research groups [23][24][25][26][27] have shown that using a two-step wave front shaping combined with temporal focusing (TF) [28][29][30][31] it is possible to generate multiple high resolution extended light patterns in 3D, a technique we named multiplexed temporally focused light shaping (MTF-LS). These approaches led to the first demonstrations of neural circuit manipulation in 3D 25,26 , yet the need of using conventional high numerical aperture (NA) objectives limited their use to circuits in superficial (≤ 300 µm) cortical areas or to in-vitro applications.…”
Section: Introductionmentioning
confidence: 99%